Chứng minh rằng:
1/1.2= 1/1-1/2;...; 1/n(n+1)=1/n-1/n+1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A= \(\frac{1}{2}\) + \(\frac{1}{2^2}\) + \(\frac{1}{2^3}+\frac{1}{2^4}+...+\frac{1}{2^{100}}\)
\(\Rightarrow\) 2A = 1 + \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+...+\frac{1}{2^{99}}\)
\(\Rightarrow\) 2A - A = ( \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+...+\frac{1}{2^{100}}\) ) -
( \(1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+...+\frac{1}{2^{99}}\))
\(\Rightarrow\) A = 1 - \(\frac{1}{2^{100}}\) < 1
Vậy: A < 1
\(\frac{1}{2}\)
B= \(\frac{2}{1.2}+\frac{2}{2.3}+\frac{2}{3.4}+...+\frac{2}{99.100}\)
= 2. \(\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{99.100}\right)\)
= 2. ( \(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{99}-\frac{1}{100}\) )
= 2. \(\left(\frac{1}{1}-\frac{1}{100}\right)\) = \(\frac{99}{50}\)
\(\Rightarrow\) B = \(\frac{99}{50}\) < \(\frac{100}{50}\) = 2
Vậy: B < 2
Ko bt đúng ko .
Đặt A=1.2+2.3+3.4+...+n(n+1)
A=1.2+2.3+3.4+...+n(n+1)
=>3A=(3−0)1.2+(4−1)2.3+...+(n+2−n+1)n(n+1)=>3A=(3−0)1.2+(4−1)2.3+...+(n+2−n+1)n(n+1)
=>3A=1.2.3−0.1.2+2.3.4−1.2.3+...+n(n+1)(n+2)−(n−1)n(n+1)=>3A=1.2.3−0.1.2+2.3.4−1.2.3+...+n(n+1)(n+2)−(n−1)n(n+1)
=>3A=n(n+1)(n+2)=>3A=n(n+1)(n+2)
=>A=n(n+1)(n+2)3=>A=n(n+1)(n+2)3 (đpcm)
a: B=1-1/2+1/2-1/3+...+1/2020-1/2021
=1-1/2021=2020/2021
b:
1/2^2+1/3^2+...+1/2021^2>0
=>A>1
1/2^2+1/3^2+...+1/2021^2<1-1/2+1/2-1/3+...+1/2020-1/2021=2020/2021
=>A<2020/2021+1
mà A>1
nên 1<A<1+2020/2021
=>A ko là số nguyên